Evidence for marine production of monoterpenes - Yassaa, N.; Peeken, Ilka; Zöllner, Eckart; Bluhm, Katrin; Arnold, S. R.; Spracklen, D. V.; Williams, J. (Environmental Chemistry, 2008)
Environmental context. Laboratory incubation experiments and shipboard measurements in the Southern Atlantic Ocean have provided the first evidence for marine production of monoterpenes. Nine marine phytoplankton monocultures were investigated using a GC-MS equipped with an enantiomerically-selective column and found to emit monoterpenes including (–)-/(+)-pinene, limonene and p-ocimene, all of which were previously thought to be exclusively of terrestrial origin. Maximum levels of 100–200 pptv total monoterpenes were encountered when the ship crossed an active phytoplankton bloom. Abstract. Laboratory incubation experiments and shipboard measurements on the Southern Atlantic Ocean have provided the first evidence for marine production of monoterpenes. Nine marine phytoplankton monocultures were investigated using a GC-MS equipped with an enantiomerically-selective column and found to emit at rates, expressed as nmol C10H16 (monoterpene) g [chlorophyll a]–1 day–1, from 0.3 nmol g [chlorophyll a]–1 day–1 for Skeletonema costatum and Emiliania huxleyi to 225.9 nmol g [chlorophyll a]–1 day–1 for Dunaliella tertiolecta. Nine monoterpenes were identified in the sample and not in the control, namely: (–)-/(+)-pinene, myrcene, (+)-camphene, (–)-sabinene, (+)-3-carene, (–)-pinene, (–)-limonene and p-ocimene. In addition, shipboard measurements of monoterpenes in air were made in January–March 2007, over the South Atlantic Ocean. Monoterpenes were detected in marine air sufficiently far from land as to exclude influence from terrestrial sources. Maximum levels of 100–200 pptv total monoterpenes were encountered when the ship crossed an active phytoplankton bloom, whereas in low chlorophyll regions monoterpenes were mostly below detection limit.